Key Enabling Technologies and Smart Specialization Strategies. European Regional Evidence from patent data - Sandro Montresor; Francesco Quatraro (European Commission, Joint Research Centre (JRC), 2015)
The paper aims at investigating whether Key Enabling Technologies (KETs) can have a role in facilitating regional Smart Specialisation Strategies (S3). Drawing on the economic geography approach to S3, we formulate some hypotheses about the impact that KETs-related knowledge can have on the construction of new regional technological advantages (RTAs). By crossing regional data on patent applications, in KETs-mapped classes of the International Patent Classification (IPC), with a number of regional economic indicators, we test these hypotheses on a panel of 26 European countries over the period 1980-2010. KETs show a positive impact on the construction of new RTAs, pointing to a new “enabling” role for them. KETs also exert a negative moderating role on the RTAs impact of the density of related pre-existing technologies, pointing to the KETs capacity of making the latter less binding in pursuing S3. Overall, the net-impact of KETs is positive, pointing to a new case for plugging KETs in the S3 policy tool-box.
Keywords: R11; R58; O31; O33; 330; Key Enabling Technologies; Smart Specialization Strategies; Revealed Technological Advantages